2013
DOI: 10.1002/jctb.4257
|View full text |Cite
|
Sign up to set email alerts
|

A fibrous bed bioreactor to improve the productivity of succinic acid by Actinobacillus succinogenes

Abstract: BACKGROUND Succinic acid is one of the most important biorefinery platform chemicals. The fibrous‐bed bioreactor (FBB), comprising spiral cotton fiber packed in a modified bioreactor, is effective for anaerobic cell‐immobilized fermentation. In this study, fermentation production of succinic acid by Actinobacillus succinogenes using a FBB was investigated. RESULTS The effect of different initial glucose concentrations on succinic acid production in batch fermentation in a FBB was examined, which indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…To use the monomeric sugars present in pretreated sugarcane bagasse and trash, such as pentose, arabinose and cellobiose, more efficiently, the PHB bioproduct yield could be increased through additional genetic engineering and production development (i.e. fermentation) of recombinant E. coli, similarly to what has been done to the SA‐producing micro‐organism A. succinogenes …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To use the monomeric sugars present in pretreated sugarcane bagasse and trash, such as pentose, arabinose and cellobiose, more efficiently, the PHB bioproduct yield could be increased through additional genetic engineering and production development (i.e. fermentation) of recombinant E. coli, similarly to what has been done to the SA‐producing micro‐organism A. succinogenes …”
Section: Resultsmentioning
confidence: 99%
“…An SA seed train provided inoculum to minimize the micro‐organism's lag phase and promote exponential growth using the typical size of 10% (v/v) of the fermentation volume . Ninety percent of the feed stream was therefore pumped to the fermentation area and preheated prior to fermentation at 38°C . The nutrient medium, which was used in the seed train and fermentation area, was sterilized at 120°C for 15 min.…”
Section: Biorefinery Process Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugarcane bagasse, a lignocellulose material, is the major by‐product of the sugar cane industry . The bagasse surface is arranged in a crisscross pattern by the fiber matrix, which can increase the surface area to support cell attachment.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, a succinic acid production of 129.21 g L −1 with a productivity of 2.15 g L −1 h −1 was achieved under a same fermentation condition via the overexpression of mgtA in KMG111 to increase the concentration of intracellular Mg 2+ . Ma et al [15] obtained a production of 79.0 g L −1 succinic acid by using a nonrecombinant E. coli strain (AFP11), but their overall productivity of 1.05 g L −1 h −1 is relatively lower, It was also reported that A. succinogenes could produce 39.0 g L −1 succinic acid with a productivity of 3.61 g L −1 h −1 and a yield of 0.85 g g −1 glucose [34] and C. glutamicum is able to produce 146 g L −1 succinic acid in 46 h with a productivity of 3.17 g L −1 h −1 [22]. But, the high productivity was achieved under the high cost fermentation media.…”
Section: Dual-phase Fermentation In a 3-l Bioreactormentioning
confidence: 98%